Effect of Vitamin E on some blood and biochemical parameters in ewes - Al-Judi, A. M.H . (The Iraqi Journal of Veterinary Medicine, 2005)
The effect of vit.E in feed blocks to ewes were studied in ewes on thefollowing parameters; Hemoglobin concentration, Packed Cell Volume,differential leukocytic count, total protein, albumin, and globulin ratios. Therewere a significant decrease in Hb concentration & PCV after two,& four weeks,there were no significant differences in the percentage of lymphocytes,neutrophils,& eiosinophils, & with a significant increase in monocytepercentage.There was no significant different in total protein ratio, while the ratio ofalbumin decreased significantly after 2 & 4 weeks, with a significant increase inthe globulin ratio at the same period.